Innovative Advanced Materials for Energy Storage and Beyond Synthesis, Characterization and Applications - Thakur, Vijay Kumar (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This highly informative and carefully presented book covers the most recent advances as well as comprehensive reviews addressing novel and state-of-the-art topics from active researchers in innovative advanced materials and hybrid materials, concerning not only their synthesis, preparation, and characterization but especially focusing on the applications of such materials with outstanding performance.